Comparative and competitive advantage of soybean cultivation in Noakhali and Laxmipur District of Bangladesh (Journal of the Bangladesh Agricultural University, 2016)
The study highlighted different socio-economic aspects of soybean cultivation in Noakhali and Laxmipur district of Bangladesh. The issues were: cost and return of soybean and its competing crops cultivation, competitive and comparative advantage of soybean production, constraints to higher production, and farmers attitudes towards soybean cultivation in Bangladesh. The average yield of soybean, groundnut, cowpea and grasspea were 1813kg/ha, 1473kg/ha, 871kg/ha and 1076kg/ha, respectively. The net return received from soybean, groundnut, cowpea and grasspea cultivation were estimated at Tk. 25599/ha, Tk. 17047/ha 11805 and Tk. 8825/ha, respectively. The average benefits cost ratios of soybean, groundnut, cowpea and grasspea production were 1.43, 1.26, 1.28 and 1.29 over full cost, respectively. The estimated DRC value for soybean production was found 0.55 which clearly indicate that the production of soybean in Bangladesh has comparative advantage rather than import. Functional analysis showed that TSP, MP, gypsum and pesticide use had positive significant impact on soybean cultivation. Although the cultivation of soybean was found to be profitable, many farmers showed negative attitudes toward its production. Scarcity of chemical fertilizers with its peak price, lack of HYV seed availability, lack of technical knowledge and natural calamities were found as the barriers of soybean crops expansion in Noakhali and Laxmipur district of Bangladesh.J. Bangladesh Agril. Univ. 13(2): 265-272, December 2015